Application of ultraviolet light sources for in vivo disinfection. (17th September 2021) - Ou, Yiyu; Petersen, Paul Michael
Abstract: Development of antibiotic resistance is a major challenge for antibiotics as an effective treatment approach of infectious diseases and pathogenic microbes with resistance to antibiotics will become difficult to be treated. Therefore, a new therapy method, which is safe and can inactivate pathogenic microbes effectively without developing a resistance, is highly needed. Ultraviolet irradiation is well known for its ability of effective microbial inactivation and it is widely used in sterilization of inanimate objects based on conventional ultraviolet light sources. Meanwhile, applying ultraviolet irradiation in human disinfection application is an emerging and rapidly progressing field. This review focuses on recent studies in ultraviolet based disinfection methods including both animal and human studies. We will introduce different microbial inactivation mechanisms, which are associated with the ultraviolet irradiation wavelength. Relevant research work will be summarized with a focus on their microbial inactivation effect and safety issues.